1992
DOI: 10.1536/ihj.33.95
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Visualization of Pulmonary Blood Flow Velocity Profiles in Lambs

Abstract: SUMMARYFor a better understanding of the characteristics of blood flow in the pulmonary artery, we constructed three-dimensional images of velocity profiles of blood flow in the pulmonary artery from pulsed Doppler ultrasound recordings in 14 lambs aged 28-40 days. In 8 lambs, pulmonary hypertension was created by the central venous injection of monocrotaline pyrrole. Six lambs served as unaltered controls. The velocity data were sampled in 2mm increments along both an anterior-posterior axis and a right-left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In certain respects, out data correspond to those obtained by other in vivo studies [13,18,[20][21][22][23]. One diameter downstream of the pulmonary valve, a systolic skewed velocity profile with the highest velocities at the inferior to right superior vessel wall was found in all cases during systole.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In certain respects, out data correspond to those obtained by other in vivo studies [13,18,[20][21][22][23]. One diameter downstream of the pulmonary valve, a systolic skewed velocity profile with the highest velocities at the inferior to right superior vessel wall was found in all cases during systole.…”
Section: Discussionsupporting
confidence: 87%
“…The less pronounced rotational phenomena in the present study might have been caused by the smaller number of measuring points used to cover the crosssectional area (41 vs 17 points). Frantz et al [18], Lucas et al [20,22], and Katayama et al [23] found no rotational phenomena. This could have been caused by a lower spatial resolution as their measurements in the main pulmonary artery were carried out along one or two diameters.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A detailed three-dimensional analysis of waveform shapes and velocity profiles observed during the acceleration and deceleration phases of systole in a subset of the controls and monocrotaline pyrrole animals has been published [30]. Though the general waveform shape persisted throughout the vessel cross-section, some variability with position was observed.…”
Section: Waveform Skewmentioning
confidence: 99%